Rewriting Westphalia and Reviving Bandung: The Historical Trajectory of Nahdlatul Ulama’s Global Islamic Vision - Sus Eko Ernada (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2025)
This paper explores how the Muslim world today faces a fragmentation that echoes Europe's bloody religious wars prior to the Treaty of Westphalia (1648) and the colonial subjugation that triggered the Bandung Conference (1955). At a time when sectarianism, radicalism, and external securitisation threaten the coherence of Islamic civilisation, Nahdlatul Ulama (NU), Indonesia's largest Muslim organisation, emerges as a unique actor striving for renewal. This article examines NU's global initiatives through the dual historical lenses of Westphalia and Bandung, proposing that NU seeks not only to establish a